PENINGKATAN EFEKTIVITAS PELAYANAN PUBLIK MELALUI REDESIGN PROSES BISNIS INSTANSI PEMERINTAH - Bahdin Nur Tanjung; Parlaban Karo-Karo; Imanuel Sembiring (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program (PKM) activity aims to improve the effectiveness of public services through business process redesign at partner government agencies. Common problems encountered include long and repetitive service flows, non-standard requirements, high queues, uncertain completion times, and a lack of traceability of service status. The program is implemented through as-is process mapping, cycle time and bottleneck measurement, root cause analysis, to-be process design (step simplification, reduced handoffs, document standardization, and role refinement), SOP and SLA development, and implementation training and trial assistance. The main outputs are new process maps, service SOPs, SLAs/service time standards, forms/checklists, and service performance indicators. Improvements are targeted at reducing service times, increasing service certainty, and increasing user satisfaction.